Achieving the Paris Climate Agreement goals : global and regional 100% renewable energy scenarios with non-energy GHG pathways for +1.5°C and +2°C /: global and regional 100% renewable energy scenarios with non-energy GHG pathways for +1.5°C and +2°C. (2019) - Unknown
No abstract available